Relatos autobiográficos à luz da pedagogia de gêneros: uma trajetória com intervenção em classe de alunos de PROEJA - Oliveira, Sandra Maria do Nascimento de (2017)
The term “Sydney School” was coined in 1994, in reference to the work with language and education that had been carried out in the Department of Linguistics, at the University of Sydney for at least a decade. The project spread throughout schools and universities in Australia. It became an international movement, which aimed, initially, at developing a writing pedagogy to support students in succeeding in tasks demanded by the school (ROSE; MARTIN, 2012, p. 1). In view of that, the purpose of this study is to evaluate whether a proposal of work based on genres, in light of the Sydney School perspective and the Teaching and Learning Cycles (MARTIN; ROSE, 2008; ROSE; MARTIN, 2012), could be adapted to the reality and specificities of a group of Youth and Adult Education students. Five specific objectives are addressed: (a) to identify the linguistic competence of the students in regards to reading and writing; (b) to organize, apply and monitor a Work Plan, using the autobiographical genre during a school year; (c) to monitor the implementation of the Work Plan, maintaining a dialogical attitude towards the students’ preferences, needs or weaknesses; (d) to perform diagnostic evaluative assessments during all the stages of the work; (e) to compare the writing process, in terms of linguistic competence development. In order to achieve these objectives, we proposed to the class the production of autobiographical recounts in light of the premises of the Sydney School, for which the sequenced application of the three stages of the learning cycle that constitute the Pedagogy of Genres was applied: Deconstruction, Joint Construction and Independent Construction. This methodological choice is due to an outstanding feature of this pedagogy, which is its focus on the preparation of students to perform and succeed in individual writing tasks. Prior to the application of the cycle, the students produced autobiographical recounts whose assessment resulted in regular scores predominantly. In the Deconstruction phase, we presented model texts and activities of reading, writing, and linguistic analysis, in order to describe and analyze the autobiographical recount genre. In the Joint Construction phase, the students produced a recount with the teacher and colleagues. Finally, in the Independent Construction phase, the students produced their texts individually. The assessment of their text production showed an improvement in their scores to good and very good. After the completion of these three cycles, some spelling and sentence organization issues were still noted in the texts. Because of this, we designed and applied activities in the systemic-functional perspective to minimize the inadequacies found. As the main result of this work, the students' scores predominantly improved to good and very good during the process of production of the autobiographical recount. Consequently, they developed awareness about the genre, by identifying the features that define it, as well as reflected on the use of language and analyzed it semantically and functionally.